Penggunaan Prosedur Denda untuk Mengurangi Perilaku Keluar dari Tempat Duduk Siswa Tunagrahita yang Hiperaktif di SLB Feybe Mangaran Kabupaten Talaud - Elise P. Sumaa (Peneliti.net, 2020)
This study aims to obtain an overview of the use of the fine procedure to reduce the behavior of leaving the seat of hyperactive children in SLB Feybe Mangaran Kab. Talaud. The research method used is a single subject research (single subject research) or SSR which is an experimental research that focuses more on individual scores or performance rather than group performance. Based on the research results previously described, the conclusions are as follows: 1) Walking behavior in the class of mentally retarded students who are hyperactive in SLB Feybe Mangaran Kab. Talaud, greatly influences the classroom situation and affects children's development, so that early on children need appropriate intervention, 2) The fine procedure in the form of canceling the star stamp on children's books, can reduce the behavior of walks in the class of hyperactive mentally retarded students at SLB Feybe Mangaran Kab. Talaud, quite effective, because it can reduce the child's behavior by up to 65%, 3) The effect of the intervention procedure of fines on students with mental retardation who are hyperactive, can be stable or are maintained at home. With the results of this study, the researchers suggest that in order to increase the results of implementing this procedure, the teacher must combine it with other procedures, such as positive reinforcement, so that other non-adaptive behaviors can be prevented first. In addition, it is necessary to conduct training on behavior modification for teachers.